Plant propagation by tissue culture 3rd edition (Springer, 2008)
For researchers and students, George’s books have become the standard works on in vitro plant propagation. For this, the third edition of the classic work, authors with specialist knowledge have been brought on board to cover the hugely expanded number of topics in the subject area. Scientific knowledge has expanded rapidly since the second edition and it would now be a daunting task for a single author to cover all aspects adequately. However, this edition still maintains the integration that was characteristic of the previous editions. The first volume of the new edition highlights the scientific background of in vitro propagation. The second volume covers the practice of micropropagation and describes its various applications.